α5β1 Integrin-Fibronectin Interactions Specify Liquid to Solid Phase Transition of 3D Cellular Aggregates - Caicedo-Carvajal, Carlos E. (Public Library of Science, 2010)
BACKGROUND: Tissue organization during embryonic development and wound healing depends on the ability of cells on the one hand to exchange adhesive bonds during active rearrangement and on the other to become fixed in place as tissue homeostasis is reached. Cells achieve these contradictory tasks by regulating either cell-cell adhesive bonds, mediated by cadherins, or cell-extracellular matrix (ECM) connections, regulated by integrins. Integrin α5β1 and soluble fibronectin (sFN) are key players in cell-ECM force generation and in ECM polymerization. Here, we explore the interplay between integrin α5β1 and sFN and its influence on tissue mechanical properties and cell sorting behavior. METHODOLOGY/PRINCIPAL FINDINGS: We generated a series of cell lines varying in α5β1 receptor density. We then systematically explored the effects of different sFN concentrations on aggregate biomechanical properties using tissue surface tensiometry. We found previously unreported complex behaviors including the observation that interactions between fibronectin and integrin α5β1 generates biphasic tissue cohesion profiles. Specifically, we show that at constant sFn concentration, aggregate cohesion increases linearly as α5β1 receptor density is increased from low to moderate levels, producing a transition from viscoelastic-liquid to pseudo viscoelastic-solid behavior. However, further increase in receptor density causes an abrupt drop in tissue cohesion and a transition back to viscoelastic-liquid properties. We propose that this may be due to depletion of sFn below a critical value in the aggregate microenvironment at high α5β1 levels. We also show that differential expression of α5β1 integrin can promote phase-separation between cells. CONCLUSIONS/SIGNIFICANCE: The interplay between α5-integrin and sFn contributes significantly to tissue cohesion and, depending on their level of expression, can mediate a shift from liquid to elastic behavior. This interplay represents a tunable level of control between integrins and the ECM that can influence tissue cohesion and other mechanical properties, which may translate to the specification of tissue structure and function. These studies provide insights into important biological processes such as embryonic development, wound healing, and for tissue engineering applications.